Analyze the relationship of brand image and advertisement towards decision to become a customer on bank BNI Batam branch - Guci, D.A.; Ghazali, P.L.; Nst, A.M.; Fajrillah, .; Abas, S.; Fadhli, M. (2020)
The aim of this research is to explore the relationship of brand image and advertisement towards decision to become a customer on Bank BNI Batam Branch. A hundred respondents of people who have become a customer on Bank BNI Batam Branch have been chosen in the field of research in Batam, Indonesia. The methode instrument was using questionnaires and made up of five variables. The questionnaires distributed were made up of three variables, where two were independent variables and one was dependent variable. By using multiple regression analysis, it is found that each independent variable has strong correlation with the single variable. it can be concluded that the brand image and advertisement have a positive relationship.